Search after method : sensing, moving, and imagining in anthropological fieldwork - Laplante, Julie; Gandsman, Ari; Scobie, Willow (Methodology and history in anthropology, 2020)
"Reigniting a tradition of learning by experience, Search After Method is a plea for more lively forms of anthropology. The multiple voices resonating in the collection come from anthropologists in all walks of academia as well as outside of it. The chapters relate the contributor's first experiences of working in the field and use their experiences to link their work to the discipline of Anthropology, along with other broader fieldwork questions. This book thus provides a powerful introduction to lived experiences of contemporary fieldwork"--